Computational Investigation on the Effects of Two-Way Wing Morphing Strategy in the Critical Mach Number - John,Bruce Ralphin Rose (2018)
ABSTRACT: The elasto-flexible wing morphing is an advanced methodology to achieve higher lift-to-drag (L/D) ratio for the subsonic wing configurations at the given flow conditions. The present article describes mechanisms of continuous morphing of a swept back wing for achieving effective delay in the critical Mach number (Mcr) distribution over the wing surface with higher L/D ratio. Firstly, typical wing sweep angles of a Jet transport airplane ranging from 25º to 32º are considered for the present investigation towards sweep morphing. Then, the planform morphing is done by increasing the value of mean aerodynamic chord by 2.5% to 7.5% from its baseline value. A novel computational simulation technique is utilized to observe the value of Mcr over the wing at each 0.5% incremental chord values. The computational fluid dynamic analysis of a 3-D doubly tapered wing model is done at 0º angle of attack and free stream Mach number about 0.85. A NACA 6-series supercritical airfoil is selected for the wing design that resembles the wing configuration of an A300-B4 airplane. The outcome of the investigation has revealed reduced drag benefits near the transonic regime through the two-way wing morphing strategy and the results are presented with applications.